The Strength of the Peace Deed in the Settlement of Land Disputes Through Mediation at the Karawang Regency Land Office - Fobia, Bella Febriani; Tehupeiory, Aartje; Napitupulu, Diana R.W. (Jurnal Indonesia Sosial Sains, 2025)
Land dispute resolution through mediation is one of the alternative methods regulated in Article 44 Paragraph (5) of the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning the Handling and Settlement of Land Cases. This study aims to examine the legal strength of peace deeds produced through the mediation process at the Karawang Regency Land Office, as well as the effectiveness of its implementation in resolving land disputes. The method used is a normative juridical approach with reference to legal documents, legal doctrines, and interviews with relevant sources. The results of the study show that the peace deed has binding legal force equivalent to a court decision with permanent legal force, but its effectiveness in the field is still low due to factors such as lack of public understanding, the ego of the parties to the dispute, and the low level of attendance in the mediation process. To increase the success of mediation, it is recommended that BPN be more active in socialization, increase the capacity of mediators, and strengthen legal arrangements related to peace deeds so that they can be more reliable in the process of resolving land disputes.